Muhadharah Sebagai Media Pengembangan Kompetensi Public Speaking Siswa: Studi Pada MTS Mambaul Ulum Bengkulu Tengah - Rasman; Jarni Mistika (Fakultas Agama Islam Universitas Muhammadiyah Bengkulu, 2026)
ABSTRACT Public speaking skills are essential communication competencies that students need to develop in order to effectively convey ideas and information in academic and social contexts. However, many students still experience difficulties in speaking in front of an audience due to a lack of confidence and limited opportunities for structured speaking practice. Therefore, learning media that facilitate continuous communication training are necessary to support the development of students’ speaking competencies. This study aims to analyze the role of muhadharah activities as a medium for developing students’ public speaking competencies at MTs Mambaul Ulum Bengkulu Tengah. This research employed a qualitative method with a descriptive approach. Data were collected through observations of muhadharah activities, interviews with supervising teachers and students, and documentation related to the implementation of the program. The analysis was guided by public speaking theory which emphasizes the ability to deliver messages clearly, systematically, and confidently before an audience. The findings indicate that muhadharah activities are conducted regularly and systematically with guidance from teachers prior to students’ performances. These activities contribute positively to the development of students’ public speaking competencies, including increased confidence in speaking before an audience, improved fluency in delivering speech materials, better mastery of speech content, and stronger self-confidence. Continuous practice through muhadharah activities enables students to become more accustomed to speaking in public and to communicate their ideas more effectively. Therefore, muhadharah can function as an effective medium for developing students’ public speaking competencies at MTs Mambaul Ulum Bengkulu Tengah. Keywords: Communication Competence, Muhadharah, Public Speaking, Students.